Application of KW21 Fertilizer to Increase The Cell Density and Daily Growth Rate of Chlorella sp - Kristiana, Indra (MARLIN, 2025)
This research aims to analyze the effect of enriching KW21 fertilizer with different doses on the density and growth of Chlorella sp. KW21 fertilizer is a liquid fertilizer containing high levels of the chemical nitrogen and is quite reliable for laboratory scale microalgae culture. Research method was carried out using 3 treatments with 6 repetitions. The treatments given were treatment P0 (control with a dose of 1 ml KW21 fertilizer), treatment P1 (addition of KW21 fertilizer with a dose of 2 ml), treatment P2 (addition of KW21 fertilizer with a dose of 3 ml). The parameters observed include daily density, daily growth rate and water quality. Next, the data was analyzed descriptively, qualitatively and quantitatively. The data test used is one way anova. The research results showed that differences in the use of fertilizer doses had an effect on the growth and density of Chlorella sp. On the third to fifth day, the cell density of Chlorella sp was in the exponential phase. The treatment of adding 3 ml dose of KW21 fertilizer on the 5th day showed the best results, namely with a cell density of 3.497.083 cells/ml/day, a daily growth rate of 0,71 ± 0,04 cells/ml per day, with average water quality during culture, the temperature is 21-240C , pH 6,1-7,5, DO 4,3-6,1mg/l.